a(x+1)(x-1)+b(x-2)(x+1)+(x+1)^2=9x^2-x-10
(x+1)(a(x-1)+b(x-2)+(x+1))=(x+1)(9x-10)
a(x-1)+b(x-2)+x+1=9x-10
Now this equation is much simpler!
(a+b)x-a-2b+x+1=9x-10
(a+b)x-a-2b=8x-11
(a+b-8)x-a-2b-11=0
a+b-8=(a+2b-11)/x
I can't solve it 3 variables and 1 equations means infinite answers so yea.
Answer:
C) (a-12b)(a+12b)
Step-by-step explanation:
a^2-144b^2 = (a-12b)(a+12b)
This is the formula that when two terms squared are written with a minus sign between them their factors are the product of the original numbers once with a plus sign and once with the minus sign.
This can be explained by multiplying them.
(a-12b)
<u> *(a+12b) </u>
a²- 12ab
<u> +12ab - 144b² </u>
<u> a² +0 - 144b² </u>
We see we get the same answer as applying the formula above.
<h3>
Answer:</h3>
<u>If AB = 12units, then</u>
- A'B' = 1/2 × 12 = 6units.
<u>If C'D' = 5units, then</u>
Answer:
10
Step-by-step explanation: